Characterization of the complete chloroplast genome of an endangered aquatic macrophyte, Ottelia cordata (Hydrocharitaceae) - Hai-Xia Wang; Jian-Ling Guo; Zhi-Min Li; Yan-Hong Yu; Yong-Hong Zhang (Mitochondrial DNA. Part B. Resources, 2019)
Ottelia cordata (Wallich) Dandy (Hydrocharitaceae) is an endangered aquatic macrophyte. The complete chloroplast genome sequence of O. cordata was generated by de novo assembly using whole genome next-generation sequencing. The complete chloroplast genome was 157,879 bp in length and constructed out of four parts – a large single-copy (LSC) region of 87,672 bp, a small single-copy (SSC) region of 20,265 bp, and two inverted repeat (IRa and IRb) regions of 24,971 bp each. The genome annotation predicted a total of 117 genes, including 72 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis of 20 selected chloroplast genomes revealed that sampled species of Hydrocharitaceae formed a monophyletic clade, in which O. cordata and O. acuminata var. songmingensis formed a sister clade to Elodea canadensis.